Disseminated cystic-appearing lesions in deep spaces of the neck - Zainal Abidin, Muhammad Hosni; Mohamad, Adam; Rozhan, 'Atikah (American Medical Association (AMA), 2024)
A 65-year-old woman presented with a 2-week history of worsening, painful, right-sided neck swelling with dysphagia, odynophagia, and fever. The neck swelling started with a small lump at the upper neck, which progressively increased in size. There were no symptoms of airway obstruction or aspiration, and the patient denied any constitutional symptoms. She had no history of tuberculous contact, irradiation, preceding trauma, or alleged foreign body impaction in the throat. Examination of the neck showed multiple palpable firm to fluctuant areas of neck swelling over bilateral cervical nodal levels II, III, and V. There was also similar swelling located over the anterior neck, which was fixed and immobile. Flexible nasopharyngolaryngoscopy showed bulging of the right posterior pharyngeal wall at the level of nasopharynx and velopharynx, with pooling of saliva at the pyriform fossae and vallecullae. The vocal folds were normal and mobile. Contrast-enhanced computed tomography (CT) scan of the neck showed multiple peripherally enhancing, centrally hypoattenuating lymph nodes; an irregular thyroid mass; and a retropharyngeal fluid collection.